(untitled) (Bioagro, 2022)
Gulupa (Passiflora edulis f. edulis) is among the crops with the largest expansion rates in Antioquia (Colombia). This rapid increase has been accompanied by a rise in prevalence of vascular wilt (Fusarium oxysporum) and viral diseases. In this work, we evaluated the prevalence of four RNA viruses (SMV, CABMV, PFYMV and CMV), in addition to viruses from the genus Begomovirus and the badnavirus GBVA. The presence of viruses was investigated in 15 samples of plantlets and 15 of sexual seeds, asymptomatic and symptomatic, from crops from Eastern Antioquia. For RNA viruses, infection was determined by RT-qPCR; in the case of GBVA and begomoviruses, detection was performed using PCR. The presence of these viruses was further confirmed by HTS high-throughput sequence analysis of bulked samples (15x) which allowed the complete sequencing of PFYMV, SMV and GBVA. PFYMV and SMV were the most prevalent viruses in adult plants. PFYMV was detected in 33.3 % of symptomatic and 46.6 % of asymptomatic plants, while SMV was found in 33.3 % of symptomatic, and 20 % of asymptomatic plants. For GVBA and CMV, the prevalence was below 26.6 %. Interestingly, these four viruses had a high prevalence in sprouting seeds (SMV: 40 %, CMV: 13.3 %, PFYMV: 86.6 % and GBVA: 53.3 %) suggesting that sexual seeds are important for virus transmission in gulupa. Plantlets commercialized in the region showed significant levels of SMV (86.6 %), PFYMV (60 %), and GBVA (53.3 %). CABMV and begomoviruses were not detected in any sample. These results highlight the urgent need of implementing virus seed certification schemes for this crop.